Response to Contributors - Ferguson, Everett (Journal of early Christian studies, 2012)
"1 Their contributions advance the study of the subject and begin to fulfill my hope that the book would be a point of departure for further study of baptism, a topic central to the history of Christianity as well as contemporary Christian life and ecumenical concerns. Since preparing this response, I have had opportunity to examine Ablution, Initiation, and Baptism: Late Antiquity, Early Judaism, and Early Christianity, ed. [...]regarding the art, the late antique representations of baptism (as in the ivories, mosaics, and miniatures) were more obviously immersions than the earlier representations (in the catacombs and on sarcophagi). Regarding the administrator of baptism, I note a parallel to Augustine among eastern bishops, notably John Chrysostom and Theodore of Mopsuestia, who insisted that it was not they who baptized, but God, who simply used the hand of the human administrator of baptism. [...]they pointed out that they used the formula, "So and so is baptized in the name of Father, Son, and Holy Spirit," not "I baptize so and so in the name of Father, Son, and Holy Spirit." [...]the doctrine was "regeneration in baptism," for the authors did not attribute the regeneration to the water or the act of immersing but to the action of God, Christ, and Holy Spirit at the time of baptism.